Hyperventilation as a Predictor of Blood Donation–Related Vasovagal Symptoms. Issue 4 (May 2020) - Mennitto, Serena; Ritz, Thomas; Robillard, Pierre; France, Christopher R.; Ditto, Blaine
ABSTRACT: Objective: Most of the research on vasovagal reactions has focused on the contributions of cardiovascular activity to the development of symptoms. However, other research suggests that additional mechanisms like hyperventilation may contribute to the process. The goal of the present investigation was to examine the influences of cardiovascular and respiratory variables on vasovagal symptoms. Methods: This study was part of a randomized controlled trial investigating the effects of behavioral techniques on the prevention of vasovagal reactions in blood donors. Data from the no-treatment control group were analyzed. The final sample was composed of 160 college and university students. Observational and self-report measures of symptoms were obtained. Physiological variables were measured mainly using respiratory capnometry. Results: Although respiration rate remained stable throughout donation, change in end-tidal carbon dioxide was associated with requiring treatment for a reaction during donation (odds ratio = 0.57, 95% confidence interval [CI] = 0.41 to 0.79, p = .001) and self-reported symptoms measured in the postdonation period using the Blood Donation Reactions Inventory ( β = −0.152, 95% CI = −0.28 to −0.02, t = −2.32, p = .022). Individuals with higher levels of predonation anxiety displayed larger decreases in end-tidal carbon dioxide throughout the procedure ( F (2, 236) = 3.64, p = .043, η 2 p = 0.030). Blood Donation Reactions Inventory scores were related to changes in systolic ( β = −0.022, 95% CI = −0.04 to −0.004, t = −2.39, p = .019) and diastolic blood pressure ( β = −0.038, 95% CI = −0.06 to −0.02, t = −4.03, p < .001). Conclusions: Although the vasovagal reaction has traditionally been viewed as a primarily cardiovascular event, the present results suggest that hyperventilation also plays a role in the development of vasovagal symptoms.